Qualidade do transporte rodoviário de passageiros nos trechos Campo Grande-Bonito e Campo Grande-Corumbá - de Carvalho Martins, Daniela Woolley; Paquer, Emanoele; Schluchting, Graziella (Multitemas, 2016)
__